Analysis of the Factors Affecting Customer Preference Towards McDonald’s - Ee, Chin Guan; Ibrahim, Haslindar; Gulati, Chanda; Chok, Colyin; Shanshan, Dong; Ananda, Durgahsineey A/P; Kushwah, Divya; Choudhary, Devesh; Jain, Akshat; Maron, Alif Rayhan; Kee, Daisy Mui Hung; Musyaffa, Shidqi (International Journal of Tourism and Hospitality in Asia Pasific, 2024)
Fast food is currently gaining popularity and becoming a global trend. Fast food is the most popular option among people because it is consumed quickly and cheaply. Consuming fast food is a result of a change in lifestyle from the past. It encourages workers or individuals to eat fast food rather than prepare their own meals. Therefore, despite having several of its closest rivals, such as Burger King, Pizza Hut, KFC, etc., McDonald’s is still one of the largest and most recognizable fast-food chains in the world.  This paper aims to examine and analyze the factors that influence customers’ preference toward McDonald. An online survey questionnaire was used for data collection, this survey will involve 100 respondents who have consumed Mcdonald’s. The results of this study will help us to better grasp customers’ perceptions of Mcdonald’s.